The development of coping strategies for young people to construct their identity in times of the COVID-19 pandemic - Valérie Cohen-Scali (AOSIS, 2021)
Background: The global coronavirus disease 2019 (COVID-19) pandemic has had a major impact on young people across the world. Many students struggle to complete their studies amidst the pressure of the pandemic and have many difficulties constructing their identity and career which is crucial at this period of life. An overview of the main effects of the pandemic on their identity and career development is presented.